Analisis Efisiensi Daya Pembangkit Listrik Tenaga Hybird Panel Surya Dan Mikro Hidro Di Taman Airlangga Desa Pataan Kecamatan Sambeng Kabupaten Lamongan - Karimatun Nisa; Rafli Hafidz Alfanani (Nucleus Journal, 2022)
Abstract- Renewable energy may be one of the breakthroughs in terms of power plant innovation that utilizes natural resources including wind, water, sun and so on. The combined (Hybird) PLTMH (Micro-Hydro Power Plant) and Solar Panels as alternative energy are expected to have more benefits and can overcome the lack of knowledge of the village community about Mikho Hydro Power Plants, Solar Panels whose sources of electrical energy are natural, namely water and sun. In this study, the power efficiency calculations will be carried out on solar power plants and micro hydro power plants installed in Airlangga Park, Pataan Village, Sambeng District, Lamongan Regency.